A NEW TREND IN TREATING OSTEOPOROSIS WITH BISPHOSPHONATES IN DENTAL PATIENTS IS DRUG HOLIDAYS: FOR WHOM, WHEN AND FOR HOW LONG? (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article discusses the problems of the treatment of osteoporosis in dental patients and the expediency of long breaks (so-called medicinal vacations in the treatment of bisphosphonates. The mechanism of action and clinical efficacy of bisphosphonates, particularly zoledronic acid, which has the most pronounced antiresorptive effect compared with other bisphosphonates used for the treatment of osteoporosis, are considered. The clinical and pathogenetic rationale for drug holidays is presented, and possible indications and contraindications for drug holidays in bisphosphonate therapy are considered in detail. It is concluded that the question of the possibility of prescribing and duration of medicinal vacations should be decided by a doctor individually for each patient with osteoporosis receiving bisphosphonate therapy.